FAKTOR FAKTOR YANG MEMPENGARUHI PEMBELAJARAN ORGANISASI DAN KECEPATAN PENGEMBANGAN PRODUK BARU - Amelia Ikayanti (Universitas Katolik Soegijapranata Semarang, 2013)
This research focuses on the factors - factors that affect organizational learning and new product development speed. This research seeks to examine whether the communication frequency, bi-directional communication, and communication quality can affect the organizational learning through functional conflict, and to examine whether the organizational learning can affect the new product development speed. In addition, this study also intends to seek the support of empirical evidence on the effect of communication frequency of functional conflict. Based on the analysis of the respondents (new product development team members who have been involved in the new product development process), the communication frequency, bi-directional communication, and communication quality can improve functional conflict. The increased of functional conflict will then improve organizational learning. Then ultimately, the increased of organizational learning will increase the new product development speed.